Safeguarding the Art of Pizza Making: Parallel Use of the Traditional Specialities Guaranteed Scheme and the UNESCO Intangible Heritage Convention. Issue 4 (29th April 2019) - Deacon, Harriet
Abstract: "Traditional" foodways are represented as an important part of cultural heritage in Europe. Two legal instruments aim to play a role in safeguarding them—namely, the Traditional Specialties Guaranteed (TSG) scheme and the 2003 UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage. These instruments are sometimes used in parallel—for example, in the TSG registration for "Pizza Napoletana" and the nomination of "the art of Neapolitan ' pizzaiuolo '" to one of the lists of the Convention. While recognizing the important role of state actors in this process, this article proposes going beyond a simple "misappropriation" thesis to look at the possible economic effects of registration and inscription.